2007
DOI: 10.1111/j.1365-2958.2007.06082.x
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism and regulation of the spxB (pyruvate oxidase) virulence factor gene by a CBS‐HotDog domain protein (SpxR) in serotype 2 Streptococcus pneumoniae

Abstract: Summary spxB-encoded pyruvate oxidase is a major virulence factor of Streptococcus pneumoniae. During aerobic growth, SpxB synthesizes H2O2 and acetyl phosphate, which play roles in metabolism, signalling, and oxidative stress. We report here the first cis-and transacting regulatory elements for spxB transcription. These elements were identified in a genetic screen for spontaneous mutations that caused colonies of strain D39 to change from a semitransparent to an opaque appearance. Six of the seven opaque colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
163
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 95 publications
(174 citation statements)
references
References 77 publications
9
163
1
1
Order By: Relevance
“…mreCD ϩ transcripts were expressed under the control of the fucose-inducible P fcsK promoter from the ectopic ⌬bgaAЈ locus (6,52). Quantitative RT-PCR and Western blotting confirmed that mreCD ϩ transcript and MreC protein were overexpressed by Ϸ5-fold or underexpressed by Ϸ2-fold from the ectopic site in the pres- The mapped P pcsB promoter, which is regulated by the WalRK Spn (VicRK) two-component regulatory system (44,50) and putative factor-independent transcription terminators (lollipops), are indicated. The bars indicate positions of probes used in Northern blots.…”
Section: Resultsmentioning
confidence: 99%
“…mreCD ϩ transcripts were expressed under the control of the fucose-inducible P fcsK promoter from the ectopic ⌬bgaAЈ locus (6,52). Quantitative RT-PCR and Western blotting confirmed that mreCD ϩ transcript and MreC protein were overexpressed by Ϸ5-fold or underexpressed by Ϸ2-fold from the ectopic site in the pres- The mapped P pcsB promoter, which is regulated by the WalRK Spn (VicRK) two-component regulatory system (44,50) and putative factor-independent transcription terminators (lollipops), are indicated. The bars indicate positions of probes used in Northern blots.…”
Section: Resultsmentioning
confidence: 99%
“…In S. mutans , VicR Sm also directly represses genes involved in competence and competence-induced bacteriocin ( comCDE and nlmC ) [113], and copY [117], part of the copYAZ operon required for copper homeostasis and regulation of membrane potential, competence, and biofilm formation [129]. In S. sanguinis , VicRK Ss does not regulate gtfP , a unique gene encoding a glucosyltransferase for the synthesis of soluble glucan [90] but does regulate spxB encoding pyruvate oxidase, required for conversion of pyruvate, inorganic phosphate, and O 2 to H 2 O 2 , CO 2 , and AcP [130]. Production of H 2 O 2 by S. sanguinis inhibits the growth of the competitor species S. mutans [131].…”
Section: Vicrk Regulons Of Tcss Are Diverse and Species-specificmentioning
confidence: 99%
“…Most mutant strains used in this study were derived from strains IU1824 and IU1945, unencapsulated derivatives of serotype 2 S. pneumoniae strain D39 (IU1690) (see Table S1 in the supplemental material). Strains containing antibiotic markers were constructed by transforming linear DNA amplicons synthesized by overlapping fusion PCR into competent pneumococcal cells as described previously (34)(35)(36). Primers used for the generation of amplicons are listed in Table S2.…”
Section: Methodsmentioning
confidence: 99%
“…For antibiotic selection, TSAII BA plates contained 250 g kanamycin ml Ϫ1 , 150 g spectinomycin ml Ϫ1 , 0.3 g erythromycin ml Ϫ1 , 250 g streptomycin ml Ϫ1 , or 2.5 g chloramphenicol ml Ϫ1 . In most experiments, strains were cultured statically in Becton-Dickinson brain heart infusion (BHI) broth at 37°C in an atmosphere of 5% CO 2 , and growth was monitored by the optical density at 620 nm (OD 620 ) as described previously (34)(35)(36). Where indicated, bacteria were grown in a chemically defined medium (CDM) containing 1.0% (wt/vol) glucose or 1.0% (wt/ vol) galactose as the carbon source (44).…”
Section: Methodsmentioning
confidence: 99%